CURRENT STATE OF DEVICES FOR MEASURING PHYSICAL QUANTITIES - Osadchuk, Oleksandr; Osadchuk, Iaroslav (European Science, 2025)
The paper analyzes publications devoted to theoretical and experimental research of radio-technical devices for measuring physical quantities in wireless sensor networks of control and management systems, showing that the creation of radio-technical devi